Book review: Walravens, Hartmut: Joseph Francis Rock: Travels in Eastern Tibet - Ferguson, David K. (ERDKUNDE, 2024)
Walravens, Hartmut (2024): Joseph Francis Rock: Travels in Eastern Tibet. Harrassowitz Verlag. Wiesbaden (Asien- und Afrika-Studien der Humboldt-Universität zu Berlin, Band 61). 193 pp, 4 photographs, 1 map. ISBN 978-3-447-12186-6 (paperback, 48 €), 978-3-447-39524-3 (e-book).